2020
DOI: 10.1111/jhn.12803
|View full text |Cite
|
Sign up to set email alerts
|

Short bowel syndrome and the impact on patients and their families: a qualitative study

Abstract: Background Short bowel syndrome (SBS) is a malabsorptive condition that can result in intestinal failure (SBS‐IF). Many patients with SBS‐IF require home parenteral nutrition (PN) for survival. However, PN has profound effects on patients and their family members. The present study aimed to understand the lived experience of SBS‐IF for patients and their families. Methods In‐depth semi‐structured qualitative interviews were conducted with 15 patients with SBS‐IF and five adult family members living with someon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(50 citation statements)
references
References 36 publications
1
37
0
2
Order By: Relevance
“…The fact that weaning off PN was associated with improved HRQOL for the families in our secondary analysis further validates the adverse effect that long‐term PN may have on family quality of life. Other recent studies have identified a negative effect of home PN on the HRQOL of the patient and household 20–22 . To our knowledge, this is the first study to use the PedsQL FIM methodology to assess the effects of long‐term home PN on family HRQOL.…”
Section: Discussionmentioning
confidence: 90%
“…The fact that weaning off PN was associated with improved HRQOL for the families in our secondary analysis further validates the adverse effect that long‐term PN may have on family quality of life. Other recent studies have identified a negative effect of home PN on the HRQOL of the patient and household 20–22 . To our knowledge, this is the first study to use the PedsQL FIM methodology to assess the effects of long‐term home PN on family HRQOL.…”
Section: Discussionmentioning
confidence: 90%
“…The majority (19/22) of studies employed a qualitative design (Ang et al., 2019; Asiedu et al., 2018; Bjuresäter et al., 2012; Brotherton et al., 2006; Cohen et al., 2012; Green et al., 2019a, 2019b; Halliday et al., 2017; Jukic et al., 2017; Mayre‐Chilton et al., 2011; Mori et al., 2019; Orrevall et al., 2005; Penner et al., 2012; Rickman, 1998; Sezer et al., 2020; Smith et al., 1993; Sowerbutts et al., 2020; Stavroulakis et al., 2016; Xue et al., 2021) and three were mixed methods (Fuhr & Ciachi, 2019; Kurien et al., 2017; Rickman, 1998). Data were collected predominantly through interviews (19/22) (Ang et al., 2019; Asiedu et al., 2018; Bjuresäter et al., 2012; Brotherton et al., 2006; Cohen et al., 2012; Fuhr & Ciachi, 2019; Green et al., 2019a, 2019b; Halliday et al., 2017; Kurien et al., 2017; Orrevall et al., 2005; Penner et al., 2012; Rickman, 1998; Sezer et al., 2020; Smith et al., 1991; 1993; Sowerbutts et al., 2020; Stavroulakis et al., 2016; Xue et al., 2021) and focus groups (3/22) (Jukic et al., 2017; Mayre‐Chilton et al., 2011; Mori et al., 2019). One study used a photo‐elicitation interviewing method (Asiedu et al., 2018), and one supplemented interviews with observations of Percutaneous Endoscopic Gastrostomy (PEG) feeding practices (Sezer et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Where reported, cancer (Ang et al., 2019; Asiedu et al., 2018; Bjuresäter et al., 2012; Brotherton et al., 2006; Cohen et al., 2012; Halliday et al., 2017; Kurien et al., 2017; Mayre‐Chilton et al., 2011; Orrevall et al., 2005; Penner et al., 2012; Rickman, 1998; Sezer et al., 2020; Smith et al., 1991, 1993) and neurological conditions (Ang et al., 2019; Asiedu et al., 2018; Bjuresäter et al., 2012; Brotherton et al., 2006; Jukic et al., 2017; Mori et al., 2019; Rickman, 1998; Sezer et al., 2020; Stavroulakis et al., 2016) were the most prominent diagnosis for the care recipients. One study reported the experiences of patients with short bowel syndrome intestinal failure (SBS‐IF) and their FC (Sowerbutts et al., 2020). A variety of AN&H types were used (see Table 3 for further characteristic of individual studies).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be contrasted with decision making for PN. Patients discussing their experience of PN, refer to the treatment as life saving [9,34,35]. However, they do not discuss deliberating about the decision to start PN, probably because it was driven by clinical need.…”
Section: Discussionmentioning
confidence: 99%